Effect of thermal treatment on milling performance of pigeonpea (Cajanus cajan) - SINHA, J P; INDORE, NAVNATH S; JHA, S K (The Indian Journal of Agricultural Sciences, 2017)
Pigeonpea [Cajanas cajan (L.) Millsp.] is an important pulse crop of India. It is consumed as dehusked splits commonly, known as dhal. The hull of pigeonpea adheres tightly to the cotyledons through a gummy layer that hinders separation of hull during milling. Hence, pre-milling treatment is an essential step before milling for higher dhal recovery. Thermal pre-milling treatment was conducted at temperatures (5, 85, 105, 125°C) for varying duration (2, 4, 6, 8 min). The experiment consisting of 16 treatment combinations was conducted as per factorial CRD. Treatment at temperature 85±5°C for 4 min resulted in maximum hulling efficiency of 84.28% and finished product recovery of 53.53%, which was significantly higher than untreated sample. Losses in form of broken was found to be only 2.5%.